The Tax Sensitivity of Debt in Multinationals: A Review - Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2015)
The OECD in its BEPS action plan 4 addresses tax base erosion by profit shifting through the use of tax deductible interest payments. Their main concern is interest deductions between outbound and inbound investment by groups. Studies of multinational firms show that the tax sensitivity of debt is more modest than what one would expect given the incentives for profit shifting. The purpose of this paper is to review existing literature and to add new knowledge on multinational firm behavior that pertains to the use of debt.
Keywords: H25; G32; F23; 330; corporate taxation; multinationals; capital structure; international debt-shifting; tax avoidance